Construction of Generalized k-Bessel–Maitland Function with Its Certain Properties - Waseem Ahmad Khan (Hindawi Limited, 2021)
The main motive of this study is to present a new class of a generalized k-Bessel–Maitland function by utilizing the k-gamma function and Pochhammer k-symbol. By this approach, we deduce a few analytical properties as usual differentiations and integral transforms (likewise, Laplace transform, Whittaker transform, beta transform, and so forth) for our presented k-Bessel–Maitland function. Also, the k-fractional integration and k-fractional differentiation of abovementioned k-Bessel–Maitland functions are also pointed out systematically.